Lagligen grundat tvång? Om användande av tvångsåtgärderna bältesläggning och fasthållning vid behandling mot barnets vilja - Tornerefelt,Elin (2023)
In the compulsory psychiatric care of children, the coercive measures of belt restraint and physical restraint are used to administer treatment, such as medication and tube feeding, against the child's will. The coercive measures that may be used in these care settings are regulated by the Compulsory Psychiatric Care Act (LPT). The LPT permits exceptions to the constitutional protection against forced bodily intervention that everyone is guaranteed according to the Instrument of Government (IoG). The aim of this paper is to investigate how the measures of restraint used in these forced treatment situations relate to the IoG's protection of rights, and to highlight any shortcomings in the current regulation in relation to this. Based on the legal dogmatic method, I initially examine the grounds for taking the measures of belt restraint, physical restraint, and treatment without consent against children cared for under the LPT. There is no regulation that explicit expresses what measures may be used to administer the treatment. It is only indirectly apparent, by reading the articles of the LPT in combination with each other, that force may be used. Regarding how the measures relate to the protection of rights, it is noted that the measures as such constitute forced bodily intervention in the sense of the IoG. The protection may only be limited by legislation. Here I find that, in addition to the formal aspect, the legal requirement has a qualitative side in the sense that provisions restricting rights must be foreseeable to the individual, which require that the legislation is clear and can be interpreted restrictively. Finally, it is examined whether the measures can be supported by the criminal law grounds of necessity and social adequacy. It is concluded that the right of necessity meets the formal legal requirement through its regulation in the Penal Code (BrB). The principle of social adequacy, on the other hand, is not regulated, but the Supreme Court has in case law opened for the principle to be applicable to actions that constitute a restriction of rights. The overall conclusion is that the legal support for restraint (belts and phys-ical restraints) in forced treatment situations can be questioned from several aspects. Even if it is possible to derive the measures to provisions in the LPT, it is doubtful whether these provisions sufficiently meet the requirements for foreseeability and clarity imposed by the RF's rights protection. To permit the regular use of the measures for this purpose, on the basis of the criminal law exemption from liability for necessity, is problematic, given the rule's function as an exceptional provision. The scope for applying the principle of social adequacy is even more limited and uncertain, in particular because of the formal aspect of the legal requirement to limit rights.
Keywords: Förvaltningsrätt; offentlig rätt; medicinsk rätt; psykiatrisk tvångsvård; tvångsåtgärder; rättighetsinskränkningar; nödrätt; social adekvans; barnets bästa